2004
DOI: 10.1002/art.20428
|View full text |Cite
|
Sign up to set email alerts
|

U1 RNA induces innate immunity signaling

Abstract: Objective. The U1-70-kd RNP is a prominent target of autoimmunity in connective tissue diseases. In this study, we explored whether its endogenous ligand, U1 RNA, mediates a proimmune signal and may be immunogenic.Methods. We assayed the proliferation of control and MyD88-knockout splenocytes in response to in vitro-synthesized U1 RNA, and measured interleukin-6 (IL-6) and IL-8 secretion induced by U1 RNA in a human cell line competent for signaling through Tolllike receptor 3 (TLR-3) and TLR-5. Conclusion. U1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 16 publications
(16 reference statements)
2
51
1
Order By: Relevance
“…However, the 70K-immunized mice were much more likely to develop histologic evidence of MCTD-like lung disease, as determined by blinded histopathologic review, than the MaBP-immunized mice ( Based on prior findings that U1 RNA could potentially induce proimmune signals similarly to CFA (14), and given that U1 RNA would be expected to bind to both intact and apoptotic forms of 70K in vivo (21), we tested whether U1 RNA could substitute for CFA in our model. In parallel, 5 female mice between 8 and 12 weeks of age each were immunized with 50 g of the p205 form of 70K along with either 50 g of U1 RNA in (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the 70K-immunized mice were much more likely to develop histologic evidence of MCTD-like lung disease, as determined by blinded histopathologic review, than the MaBP-immunized mice ( Based on prior findings that U1 RNA could potentially induce proimmune signals similarly to CFA (14), and given that U1 RNA would be expected to bind to both intact and apoptotic forms of 70K in vivo (21), we tested whether U1 RNA could substitute for CFA in our model. In parallel, 5 female mice between 8 and 12 weeks of age each were immunized with 50 g of the p205 form of 70K along with either 50 g of U1 RNA in (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…U1 RNA was produced by in vitro transcription of an Sp64 plasmid (Promega, Madison, WI) containing a 165-base insert corresponding to the sequence of human U1 RNA, as previously described (14). U1 RNA was tested with a Limulus assay (Cambrex BioScience, Baltimore, MD) to confirm the absence of endotoxin contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the possibility that altered TLR-signalling promotes the generation of anti-nuclear antibodies in these mice, congenic B cells demonstrated hyper-responsiveness to poly(I:C), a dsRNA analogue and TLR3 ligand. These results are intriguing and suggest a novel mechanism for how inappropriate TLR signalling contributes to lupus autoimmunity.B cells normally proliferate and exhibit enhanced survival in response to signalling through the nucleic acid sensing TLRs [15,[17][18][19]. Recently it has been shown that TLR7 overexpression in mice bearing the Y autoimmune accelerator (Yaa) or a TLR7 Tg leads to increased B-cell proliferation in response to TLR7 ligands in vitro and promotes the differentiation of B cells into anti-RNA antibody-producing cells that augments lupus-like autoimmunity in vivo [20,21].…”
mentioning
confidence: 99%
“…SnRNP complexes are composed of RNPs and RNAs, including, U1-70kd RNP and its ligand, U1 RNA. Recently, U1 RNA has been shown to mimic the effects of poly(I:C), as it forms a double-stranded secondary structure that can elicit TLR3 activation [18]. Thus, autoreactive BCR recognition of this antigen could potentially stimulate TLR3 and specifically promote antiSm/RNP reactive B-cell survival and differentiation to antibodyproducing cells.…”
mentioning
confidence: 99%